Pengaruh Komunikasi dan Konten Media Sosial Instagram Terhadap Keputusan Pembelian di Sage Dish - Muhammad Bintang Adilluhung Sampurna; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The current technological development accelerates innovations in marketing, especially through sosial media, which enables companies to interact more directly with consumers and influence their decisions. This research was conducted to determine the impact of communication and Instagram sosial media content on purchasing decisions at Sage Dish. The method used in this study is a quantitative approach with non-probability sampling techniques through purposive sampling. The population in this study involved Instagram followers who have previously purchased products at Sage Dish. A sample of 210 followers was used, calculated using Slovin's formula. Data collection was carried out by distributing questionnaires and processed using Partial Least Squares 3 (PLS3). The analysis results show that both simultaneously and partially, communication and Instagram sosial media content have a significant influence on purchasing decisions at Sage Dish.